(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the treatment outcomes of neoadjuvant chemotherapy in patients with stage II–III triple-negative breast cancer (TNBC) treated at Nghe An Oncology Hospital. Methods: A descriptive study combining retrospective and prospective data was conducted on 37 patients with stage II–III TNBC who received neoadjuvant chemotherapy at the Department of Medical Oncology 4, Nghe An Oncology Hospital, between March 2023 and April 2026. Treatment response was assessed based on clinical response and total pathological complete response (tpCR). Results: The mean age of the patients was 53.1 years, with the highest proportion (62.2%) in the 40–60-year age group. Stage II and stage III disease accounted for 70.3% and 29.7% of cases, respectively. The total pathological complete response (tpCR) rate was 43.2%. A statistically significant association was observed between clinical response and tpCR (p < 0.001). However, no significant associations were found between tpCR and other clinicopathological factors, including age, menopausal status, tumor stage, nodal stage, histological subtype, histological grade, Ki-67 proliferation index, or chemotherapy regimen (all p > 0.05). All chemotherapy regimens were well tolerated, and no patient discontinued treatment because of treatment-related toxicity. Conclusion: Neoadjuvant chemotherapy achieved a relatively high total pathological complete response rate in patients with stage II–III triple-negative breast cancer. Clinical response was a significant predictor of tpCR, whereas baseline clinicopathological characteristics were not associated with pathological complete response.